Transmutation and Exclusion Figures in Mirror, a Graphic Novel by Emma Ríos and Hwei Lim - González Fernández, Helena (Madrygal. Revista de Estudios Gallegos, 2023)
What is the relationship of human beings with other species and the natural environment? Is it possible to domesticate and reify the animal periphery through science? What are the consequences of mutation? What figures allow us to identify the rebellious positions of animals and other forms of life in the face of anthropocentric arrogance? How is the subjectification of hybrid beings represented? Do the concepts of pariah and defector serve to represent exclusion and, at the same time, project a new future? Is a multi-species alliance possible? Emma Ríos and Hwei Lim are co-authors of Mirror (Image, 2016-2019), a complex and elaborate sci-fantasy graphic novel that offers a critique of humanism, the control of knowledge, animal experimentation, interplanetary travel and the intervention of the Anthropocene on the planet. Drawing on the exclusionary figures of political theory (Hannah Arendt, Eleni Varikas, Martine Leibovici) and gender and sexuality studies on relational subjectivity, the multispecies alliance and the natural environment (Donna Haraway, Marta Segarra, Preciado), the comic offers a critique of speciesism and humanity’s action on the planets, while finding in the conscious pariah and the defector an opportunity to generate alliances on the periphery of power and create a habitable world.allow us to identify the rebellious positions of animals and other forms of life in the face of anthropocentric arrogance? How is the subjectification of hybrid beings represented? Do the concepts of pariah and defector serve to represent exclusion and, at the same time, project a new future? Is a multi-species alliance possible? Emma Ríos and Hwei Lim are co-authors of Mirror (Image, 2016-2019), a complex and elaborate sci-fantasy graphic novel that offers a critique of humanism, the control of knowledge, animal experimentation, interplanetary travel and the intervention of the Anthropocene on the planet. Drawing on the exclusionary figures of political theory (Hannah Arendt, Eleni Varikas, Martine Leibovici) and gender and sexuality studies on relational subjectivity, the multispecies alliance and the natural environment (Donna Haraway, Marta Segarra, Preciado), the comic offers a critique of speciesism and humanity’s action on the planets, while finding in the conscious pariah and the defector an opportunity to generate alliances on the periphery of power and create a habitable world.